Pengaruh Keseimbangan Kehidupan Kerja dan Beban Kerja Terhadap Kinerja Karyawan PT. Dok dan Perkapalan Surabaya - Rahmadani, Arvian Azhril; Wispandono, Raden Mas Mochammad (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
This study has an objective to analyze the effect of work-life balance and workload on employee performance at PT. Dock and Shipping Surabaya. The research method used is a quantitative approach using a questionnaire as a data collection instrument. The sample of this study consisted of 100 employees selected randomly. The results of the data analysis show that work-life balance has a positive and significant effect on employee performance. This indicates that employees who are able to manage the balance between their work and personal lives tend to have better performance. On the other hand, high workload is found to have a negative and significant effect on employee performance. Employees who have excessive workloads tend to experience decreased performance due to fatigue and stress. This study suggests that the company needs to pay attention to policies that support work-life balance, such as work time flexibility and employee welfare programs to improve employee performance. Moreover, effective workload management is also important to ensure employees do not experience overwork which can reduce productivity.